Applications of Zr-Catalyzed Carbomagnesation and Mo-Catalyzed Macrocyclic Ring Closing Metathesis in Asymmetric Synthesis. Enantioselective Total Synthesis of Sch 38516 (Fluvirucin B1) - Houri, Ahmad F. (1997)
The first enantioselective total synthesis of antifungal agent Sch 38516, also known as fluvirucin B1, is described. The synthesis includes a convergent asymmetric preparation of amine 17 and acid 18, which are then united to afford diene 62. Metal-catalyzed transformations play a crucial role in the synthesis of the latter moiety. Of particular note are the diastereo- and enantioselective Zr-catalyzed alkylations, a tandem Ti- and Ni-catalyzed process that constitutes a hydrovinylation reaction, and a Ru-catalyzed alcohol oxidation to afford carboxylic acid 18. The requisite carbohydrate 38 is synthesized in a highly diastereo- and enantioselective fashion. Optical purity of the carbohydrate moiety arises from the use of the asymmetric dihydroxylation method of Sharpless; diastereochemical control is achieved through a selective dipolar [3 + 2] cycloaddition with a readily available amine serving as the chiral auxiliary. Union of the appropriately outfitted carbohydrate 71 and diene 62 through an efficient and diastereoselective glycosylation is followed by a remarkably efficient Mo-catalyzed macrocyclization that proceeds readily at room temperature.